Catalytic activity trends of pyrite transition metal dichalcogenides for oxygen reduction and evolution. Issue 33 (12th August 2022) - Lee, Wooseok; Kim, Jongseung; Kim, Heejin; Back, Seoin
Abstract : In this work, transition metal dichalcogenides are investigated as promising oxygen reduction/evolution reaction catalysts using density functional theory calculations. Multivariate regression models are also developed to predict activity descriptors. Abstract : Transition metal dichalcogenides (TMDs) have been considered as promising materials for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) electrocatalysis. While there have been numerous studies focusing on layered TMDs, the ORR and OER catalytic activity trends of various cubic pyrite TMDs have not been systematically explored yet. Herein, we investigated 12 earth abundant element-based pyrite TMDs (MX2, where M = Mn, Fe, Co, Ni and X = S, Se, Te) using density functional theory (DFT) calculations. We initially constructed surface Pourbaix diagrams to determine the most stable surface coverages under the reaction conditions and found that the oxidized surfaces are most energetically preferred in all cases. We then calculated the binding free energies of reaction intermediates (O*, OH* and OOH*) and established their scaling relations. The electrochemical ORR and OER performances were then displayed on two-dimensional volcano plots, which suggest MnS2, FeS2, NiTe2 and CoSe2 to be ORR active, and CoTe2 and CoSe2 to be OER active. In addition, we built multivariate linear regression models to predict Δ G O* and Δ G OH* using only atomic and bulk properties to readily estimate the catalytic activities of pyrite TMDs and to explore correlations between those properties. Particularly, we found that the electron affinity and bulk Bader charges of metal atoms are critical in determining the ORR and OER catalytic activities, which could be used as a guidance for future catalyst design.